The Effectiveness of ddPCR for Detection of Point Mutations in Poor-Quality Saliva Samples - Riedlova, Petra; Kramna, Dagmar; Ostrizkova, Silvie; Tomaskova, Hana; Jirik, Vitezslav (Healthcare (Basel, Switzerland), 2022)
BACKGROUND: The noninvasive collection of saliva samples for DNA analyses is simple, and its potential for research and diagnostic purposes is great. However, DNA isolates from such samples are often of inferior quality to those from blood. AIM: The aim of this study was to investigate the robustness and sensitivity of the ddPCR instrument for genetic analyses from saliva samples of poor quality by comparing their results to those obtained using an established method from blood samples. METHODS: Blood and saliva were collected from 47 university students, which was followed by manual isolation of DNA and analysis on droplet digital PCR (ddPCR). Results of analyses were supplemented with values of fractional abundances. RESULTS: ddPCR proved to be highly suitable for analysis of even low-quality saliva samples (concentrations as low as 0.79 ng/µL), especially when augmented by fractional abundance data. This combination yielded 100% agreement with results obtained from blood samples. CONCLUSION: This study verified the applicability of ddPCR as a sensitive and robust method of genetic diagnostic testing even from low-quality saliva isolates. This makes it potentially suitable for a wide range of applications and facilitates the performance of large epidemiological studies, even if sampling or sample processing is suboptimal.
Keywords: blood; point mutation; fractional abundance; saliva; ddPCR; manual isolation